The effect of liquidity ratio, solvability ratio, activity ratio and ownership structure to the company profitability of consumer goods industry in Indonesian capital market - Dimas Moch Cholil Gibran; Rohmad Fuad Armansyah (Institute of Computer Science (IOCS), 2023)
Profitability includes a company’s financial performance measurement indicator used to measure the effectiveness of the company when creating profit by the total utilization of the assets owned. There are several factors that can affect profitability: liquidity, solvency, activity and managerial ownership. The first factor is liquidity, things that should be considered in reviewing the profitability of the company is the influence of low liquidity on profitability. Researchers are looking to test their impact on liquidity, solvency, activity and managerial ownership structure on the profitability of the company. In this study, researchers gave the research limitations. There are variables used, samples studied, and research periods Profitability as a bound variable and Liquidity, Solvability, Activity and Managerial Ownership as a free variable in manufacturing companies listed in BEI 2017-2021 In this section will be explained in the discussion of multiple liner regression analysis of liquidity variables (QR), solvency (DER), activity (PP) and managerial ownership structure (KM) to profitability (ROA). Both simultaneously (f) and partial (test). Liquidity has a significant influence on profitability. Solvability has a significant influence on profitability. Activity has no significant influence on profitability. The Ownership Structure has no significant influence on profitability